Implementation of a Pilot Elementary Mathematics Specialist Endorsement Program - Robin Henrikson; Andrew Lumpe (Education Sciences, 2021)
We present the results of a mixed methods study focusing on the implementation of a pilot elementary mathematics specialist (EMS) endorsement program implemented in partnership with the several educational organizations to provide teachers in high needs rural areas an opportunity to earn the EMS endorsement through coursework and instructional leadership experiences. The data presented draw from social cognitive theory and andragogy to describe the experiences of the EMS candidates throughout their endorsement program and to provide recommendations for programmatic improvements. We sought to explore ways in which the EMS candidates’ experiences within the program and school-based internship impacted their levels of self-efficacy and perceived success within the program. We also sought to determine the opportunities and barriers that exist with the EMS candidates’ respective learning environments as they implemented professional learning plans with a core set of teachers they collaborated with to improve mathematics instruction. The results of this study indicate that both EMS candidates and the teachers they worked with increased their levels of mathematics content knowledge. EMS candidates also improved their levels of self-efficacy regarding mathematics teaching and leadership skills. Furthermore, both EMS candidates and their core set of teachers improved in time spent focused on ongoing professional learning activities. Recommendations include a need to support teachers as they expand their role into instruction as well as equip school leaders to ensure they can support teacher leadership candidates in their professional growth.